Efficacy and safety of PD-1/PD-L1 and CTLA-4 immune checkpoint inhibitors in the treatment of advanced colorectal cancer: a systematic review and meta-analysis - Song, Dandan; Hou, Shufu; Ma, Ning; Yan, Bing; Gao, Jing (Frontiers in Immunology, 2024)
were systematically searched for relevant studies. Outcomes including median progression-free survival (mPFS), median overall survival (mOS), overall response rate (ORR), disease control rate (DCR), treatment-related adverse events (TRAEs) and ≥grade 3 TRAEs were extracted for further analysis. The risk of bias was assessed by subgroup analysis.Results: 12 articles with 566 patients were identified and subjected to meta-analysis.With regard to survival analysis, the pooled mOS and mPFS were 6.66 months (95%CI 4.85-9.16) and 2.92 months (95%CI 2.23-3.83), respectively. In terms of tumor response, the pooled ORR and DCR were 21% (95%CI 6%-41%) and 49% (95%CI 27%-71%), respectively. The pooled AEs rate and ≥ grade 3 AEs rate were 94% (95%CI 86%-99%) and 44% (95%CI 30%-58%).PD-1/PD-L1 inhibitors combined with CTLA-4 inhibitors have shown promising clinical responses in the treatment of colorectal cancer (CRC). Although the incidence of adverse reactions is high, they are generally tolerable.